Statistical t-test assessment on performance of power system stabilizer for oscillation damping - Wai Myat Thu; Kyaw Myo Lin (International Journal of Applied Power Engineering (IJAPE), 2021)
The statistical operation is necessary to validate the analytical procedure since the most important common operation is the comparison of result data to quantify accuracy and precision. In this paper, a statistical process is proposed to ensure the impact of power system stabilizers (PSSs) in 202-bus, 40-machine MEPE test system. The eigenvalue analysis is utilized for detecting the lowest damping modes and evaluating the damping ratio of system oscillation, and these modes are applied as input for statistical analysis. A t-test analysis was performed on the difference of damping performance by proposed designed PSS, tuned PSS, and without PSS to support the hypothesis. The t-test results validated that the MEPE test system with designed PSS is most applicable for the improvement of oscillation damping in the power system.